Analisis dan Perancangan Antarmuka Aplikasi Wisata Menggunakan Metode User Centered Design (UCD) - Purbo, Yevi Septiray; Utomo, Fandy Setyo; Purwati, Yuli (Jurnal Teknologi Terpadu, 2023)
Lampung has many tourist attractions and natural areas that attract the attention of tourists, both domestic and foreign. However, there are still challenges in optimizing Lampung's tourism potential. One of the challenges is limited access to information regarding tourist destinations, accommodation and available activities. Apart from that, coordination between tourists and related parties such as destination managers and tourism services also need to be improved. To overcome this problem, a prototype of the VACALAM (Vacation Lampung) application was designed using Figma with the User-Centered Design (UCD) method. This research aims to increase user comfort and satisfaction in using the Vacalam application and encourage tourists to visit Lampung. In this application there are several features including ticket booking features, tour lists, trending tours, and a list of events in Lampung. The results of this research are user interface designs that follow good design principles, including simplicity, consistency, and readability. The use of colors, typography, and icons are also considered to improve the clarity and visual appearance of the application. The good user interface design and user experience have been tested using the System Usability Scale (SUS), with a final score of 71.75. These results provide guidance for other application developers in designing engaging and responsive user interfaces and user experiences using Figma.